The Relationship between Emotional Intelligence and Ethical Decision Making: A Study on Human Resources Specialists - Necare, Eda; Sehitoglu, Yasin (IGIAD-TURKISH ENTREPRENEURSHIP & BUSINESS ETHICS ASSOC, 2018)
Psychologists, philosophers and some other social scientists have studied on emotional intelligence for many years and they have made different descriptions while creating different models. Recent studies show that conscious business firms are now paying attention to emotional intelligence and try to measure it with various tests, role-playing methods, and promotions alongside education level and work experience. The level of emotional intelligence can be used as an element through which business firms can estimate people's ethical decision-making levels. This study aims to reveal the relationship among the sub-dimensions of emotional intelligence by tackling the relationship between people's emotional intelligence and their ethical decision-making through human resources specialists working in the telecommunications sector.
Keywords: Emotional intelligence; Ethical decision making; Human resources; Ethics; Business ethics; Business & Economics